Effect of Quail Egg Yolk in Tris Based Extender on Cryopreservation of Sahiwal Bull Spermatozoa - Garima Singh; Saxena, Atul; Neha Chaudhary; Kumar, Arun; Vikas Sachan; Anuj Kumar; Jitendra Kumar Agrawal (The Indian Journal of Animal Reproduction, 2024)
The present study was designed to determine the effect of different concentrations of quail egg yolk (5%, 10%, 15% and 20%) in tris based semen extender on progressive motility of Sahiwal bull spermatozoa at pre-freeze as well as post-thaw stage. The progressive motility significantly (P<0.01) improved in 10% and 15% quail egg yolk concentration at pre freeze stage whereas it increases significantly in 10% quail egg yolk concentration at post-thaw stage. The findings of the present study suggested that quail egg yolk improves post-thaw sperm progressive motility at 10% concentration.